2019
DOI: 10.1073/pnas.1818109116
|View full text |Cite
|
Sign up to set email alerts
|

Peptidic degron for IMiD-induced degradation of heterologous proteins

Abstract: Current systems for modulating the abundance of proteins of interest in living cells are powerful tools for studying protein function but differ in terms of their complexity and ease of use. Moreover, no one system is ideal for all applications, and the best system for a given protein of interest must often be determined empirically. The thalidomide-like molecules (collectively called the IMiDs) bind to the ubiquitously expressed cereblon ubiquitin ligase complex and alter its substrate specificity such that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…2b). It was reported that an N-terminal IKZF3 degron (I3D) tag did not induce degradation 11 . Therefore, to examine whether the position of the S4D tag affected the degradation of the tagged proteins, expression vectors encoding S4D-Venus or Venus-S4D were constructed, which S4D tag was fused to N-or C-terminus of Venus protein, respectively ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b). It was reported that an N-terminal IKZF3 degron (I3D) tag did not induce degradation 11 . Therefore, to examine whether the position of the S4D tag affected the degradation of the tagged proteins, expression vectors encoding S4D-Venus or Venus-S4D were constructed, which S4D tag was fused to N-or C-terminus of Venus protein, respectively ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in 2019, a peptide degron tag using the second zinc finger domain (ZNF2) of IKZF3 was reported. The tagged proteins were degraded by IMiD treatment in cultured cells and in xenograft models of kidney, breast, and brain cancer 11 . However, its use was still limited to the C-terminus of the protein of interest and overexpressed tagged proteins, not endogenous proteins 11 .…”
mentioning
confidence: 99%
“…The previously described Y130L mutant version of UBE2M was employed to modify CUL1-RBX1 with the I44A mutant version of NEDD8 39 . IKZF1 ZF2 (residues 141–169, with two point mutations K157R K165R and with a lysine added at position 140 to create a single target lysine at the N-terminus 57 was cloned with an N-terminal GST with a 3C-Prescission cleavage site and a non-cleavable C-terminal Strep-tag. IKZF1 ZF2 was purified by GST affinity chromatography, 3C-Prescission cleavage overnight, and size exclusion chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…However, degrader development is hindered by a reliance on target-specific chemical matter, which is unavailable for the majority of the proteome. To address this challenge, several strategies aimed at the direct control of cellular protein levels have been recently developed, including methods that use small molecules [3][4][5][6][7][8][9] , nanobodies 10 , or antibodies 11 .…”
mentioning
confidence: 99%